A 3D digital modelling method for railway station subgrade based on generalized hexahedron. Issue 1 (2nd January 2021) - Xu, Yang; Li, Wei; Wang, Jie; Pu, Hao; Zhang, Zhiliang; Shi, Haiou; Yuan, Quan
ABSTRACT: This study aims to propose an efficient modelling method for railway station subgrade based on cross-sectional data. A modelling principle is firstly established to determine the connection relationships between the adjacent cross sections with large differences. And the connected areas between adjacent cross sections are constructed into a solid model based on the method of 'Generalized Hexahedron'. In addition, the dissection algorithm for the solid model with multi-level topology is studied, realizing the fast cross-section extraction at an arbitrary position. The proposed method is adopted to build a 3D digital subgrade model in a real case study of Ganquan North Station. The results show that the proposed method can realize the efficient modelling and analysis of the digital subgrade model.